Interaction between ultraviolet B‐induced cutaneous hyperalgesia and nerve growth factor‐induced muscle hyperalgesia. (28th December 2015) - Lo Vecchio, S.; Petersen, L.J.; Finocchietti, S.; Gazerani, P.; Christensen, S.W.; Arendt‐Nielsen, L.; Graven‐Nielsen, T.
Abstract: Backgrounds and objectives: Clinical observations indicate that cutaneous hyperalgesia may arise from pain located in deep structures. The objective of this study was to investigate whether combined sensitization of deep and superficial somatic tissues facilitates skin hyperalgesia. Methods: The interaction between muscle and cutaneous hyperalgesia was investigated in 16 healthy volunteers. Skin sensitization was induced unilaterally on the same randomly selected part of the body by ultraviolet B (UVB) irradiation above the upper trapezius and low back muscles. The next day, muscle hyperalgesia was induced bilaterally in low back muscles by injections of nerve growth factor (NGF). Thus, 1 day after irradiation there was skin sensitization, whereas after 2 days both skin and muscle sensitizations were present. Cutaneous blood flow, pin‐prick thresholds, pressure pain thresholds (PPTs), temporal summation to repetitive painful pressure stimulation, and stimulus–response functions of graded pressure stimulations and pain intensity were assessed within the irradiated skin area and in the surrounding area before and 1, 2 and 3 days after irradiation. Results: Comparing baseline with 1 day after irradiation, UVB and UVB+NGF locations demonstrated: (1) Increased superficial blood flow inside the irradiated area ( p  < 0.01); (2) Reduced pin‐prick ( p  < 0.01) and PPTs ( p  < 0.05) within the irradiated area and in the surrounding area; (3) Left‐shifted pressure stimulus–response function within the irradiated area ( p  < 0.01); (4) Facilitated temporal summation inside the irradiated area ( p  < 0.01). Conclusions: Using skin and deep tissue pain sensitization models simultaneously, no significant synergistic effects were found within the 3‐day investigation suggesting little integration between the two phenomena in this period.